War on Ukraine: Impact on Ukrainian Medical Students - Srichawla, Bahadar Singh; Khazeei Tabari, Mohammad Amin; Găman, Mihnea-Alexandru; Muñoz-Valencia, Alejandro; Bonilla-Escobar, Francisco J. (International Journal of Medical Students, 2022)
The ongoing Russian invasion of Ukraine has taken a tremendous toll on the physical and mental wellbeing of the Ukrainian people. Accordingly, medical trainees and institutions must adapt to a high degree of uncertainty and turmoil. In 2022, Ukraine has 23 medical institutions filled with not only Ukrainian nationals but medical students from around the world. It is estimated that approximately 18,000 students from India alone study in Ukraine, many of whom are medical learners. Many of these national and foreign medical students are now displaced refugees looking to escape to Western Europe or their country of origin. Even by escaping the ongoing conflict, the question remains as to how many of these students will complete their medical education and cope with the trauma of political unrest. This is the first time that the International Journal of Medical Students Editorial Team has commented on a political conflict. We have learned in our tenure that medical students and their education worldwide is affected by many factors, including global warming and conflict. We have raised our voice before for actions to prevent climate change. We are adding our voice of support to those suffering from political unrest and acts of violence globally, with specific focus on the Ukraine. The path of war and vengeance is an easy one when compared to political dialogue and collaboration. We, the new generation of scientists of the world, claim for the use of reason over emotions to keep us all safe and promote progress worldwide.